Expression level of GAS6-mRNA influences the prognosis of acute myeloid leukemia patients with allogeneic hematopoietic stem cell transplantation. Issue 5 (21st May 2019) - Yang, Xinrui; Shi, Jinlong; Zhang, Xinpei; Zhang, Gaoqi; Zhang, Jilei; Yang, Siyuan; Wang, Jing; Ke, Xiaoyan; Fu, Lin
Abstract : As high expression level of growth arrest-specific 6 (GAS6) had an adverse effect on prognosis in acute myeloid leukemia (AML) patients, it is interesting to reveal the relationship between GAS6-mRNA level and the survival condition of AML patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT). We screened The Cancer Genome Atlas database and found 71 AML patients with GAS6-mRNA expression and received allo-HSCT treatments. We divided them into two groups based on the median expression of GAS6-mRNA. Patients with GAS6-mRNA high ( n =36) seemed to have lower bone marrow (BM) blast ( P= 0.022), lower percentage of type M5 ( P= 0.034), lower percentage of inv(16)/CBFβ-MYH11 karyotype ( P= 0.020), and lower rate of good risk classification ( P= 0.005) than the group GAS6-mRNA low ( n= 35). Higher expression level of GAS6-mRNA also brought higher RUNX1 mutations ( P= 0.003), MLL-PTD mutations ( P= 0.042), TP53 mutations ( P= 0.042), and lower NRAS/KRAS mutations ( P= 0.042). Univariate analyses showed that GAS6-mRNA was unfavorable for overall survival (OS) ( P= 0.044), as RUNX1 and WT1 also gave negative influences. Multivariate analyses confirmed that GAS6-mRNA cut down the event-free servival (EFS) and OS of AML patients with HSCT ( P= 0.029, P= 0.025). Our study indicated that higher expression of GAS6-mRNA related with adverse effects in AML patients with HSCT treatment.